Protective effects of soybean peptides on H2O2-induced oxidative injury in IPEC-J2 cells - Lu, Fushan; Yin, Qingqiang; Wang, Xiao; Xu, Lijuan; Liu, Mengjie; Zhang, Qian; Sheng, Hai; Liu, Chaoqi; Wang, Ping; Wang, Lijun; Jin, Sanjun; Li, Xinxin; et al. (Frontiers in Sustainable Food Systems, 2024)
The purpose of the study was to demonstrate how soybean peptides (SBP) protect against H2O2 -induced injury in intestinal porcine epithelial cells (IPEC-J2). SBP were prepared by protease hydrolysis, in which the molecular weights of 95.76% SBP were smaller than 3 kDa. Cell experiment included four groups: Control group (IPEC-J2 cells were treated with HGDMEM), SBP group (100 μg/mL SBP incubation for 13 h), H2O2 treatment group (1 mM H2O2 treatment for 1 h), SBP + H2O2 group (100 μg/mL SBP pretreatment for 12 h followed by 1 mM H2O2 treatment for 1 h). This study showed that that treatment with single 1 mM H2O2 for 1 h significantly reduced cell viability to 52.99% (p < 0.05), up-regulated Bax and Caspase-3 gene expressions (p < 0.05), and down-regulated gene expressions of ZO-1, CAT, SOD1, HO-1 and Nrf2 (p < 0.05), compared with the control group. However, pretreatment with SBP followed by H2O2 inducement significantly increased cell viability to 72.99%, decreased cell apoptosis, increased SOD, CAT and GSH-Px activity (p < 0.05), down-regulated Bax and Caspase-3 gene expressions (p < 0.05), and up-regulated the gene expressions of ZO-1, Claudin-1, Occludin, catalase, glutathione GPX1, SOD1, HO-1, NQO1 and Nrf2, compared with the single H2O2–induced cells. According to the study, SBP pretreatment reduced H2O2-induced oxidative stress in cells and preserved the integrity of intestinal cells.